Forms of Melanoplus bowditchi (Orthoptera: Acrididae) collected from different host plants are indistinguishable genetically and in aedeagal morphology - Muhammad Irfan Ullah; Fatima Mustafa; Kate M. Kneeland; Mathew L. Brust; W. Wyatt Hoback; Shripat T. Kamble; John E. Foster (PeerJ, 2014)
The sagebrush grasshopper, Melanoplus bowditchi Scudder (Orthoptera: Acrididae), is a phytophilous species that is widely distributed in the western United States on sagebrush species. The geographical distribution of M. bowditchi is very similar to the range of its host plants and its feeding association varies in relation to sagebrush distribution. Melanoplus bowditchi bowditchi Scudder and M. bowditchi canus Hebard were described based on their feeding association with different sagebrush species, sand sagebrush and silver sagebrush, respectively. Recently, M. bowditchi have been observed feeding on other plant species in western Nebraska. We collected adult M. bowditchi feeding on four plant species, sand sagebrush, Artemisia filifolia, big sagebrush, A. tridentata, fringed sagebrush, A. frigidus, and winterfat, Krascheninnikovia lanata. We compared the specimens collected from the four plant species for their morphological and genetic differences. We observed no consistent differences among the aedeagal parameres or basal rings among the grasshoppers collected from different host plants. Amplified Fragment Length Polymorphism markers were used to test the genetic relationships among the grasshoppers. Analysis of Molecular Variance and distance-based Unweighted Pair Group Method with Arithmetic mean dendrogram failed to reveal significant differences. Although the forms showed behavioral and minor color and size differences, the genetic data suggest all forms under study likely interbreed, which indicates they are a single species instead of four species or subspecies. These results indicate that host plant use may influence melanopline phenotype and suggest the need of further genetic analysis of subspecies recognized based on morphology, distribution, and ecology.